3D super-resolution deep-tissue imaging in living mice - Velasco, Mary Grace M.; Zhang, Mengyang; Antonello, Jacopo; Yuan, Peng; Allgeyer, Edward S.; May, Dennis; M’Saad, Ons; Kidd, Phylicia; Barentine, Andrew E. S.; Greco, Valentina; Grutzendler, Jaime; Booth, Martin J.; et al. (Optica, 2021)
Stimulated emission depletion (STED) microscopy enables the three-dimensional (3D) visualization of dynamic nanoscale structures in living cells, offering unique insights into their organization. However, 3D-STED imaging deep inside biological tissue is obstructed by optical aberrations and light scattering. We present a STED system that overcomes these challenges. Through the combination of two-photon excitation, adaptive optics, red-emitting organic dyes, and a long-working-distance water-immersion objective lens, our system achieves aberration-corrected 3D super-resolution imaging, which we demonstrate 164 µm deep in fixed mouse brain tissue and 76 µm deep in the brain of a living mouse.